2017
DOI: 10.1038/s41598-017-08434-8
|View full text |Cite
|
Sign up to set email alerts
|

Great cormorants (Phalacrocorax carbo) as potential vectors for the dispersal of Vibrio cholerae

Abstract: Vibrio cholerae is the cause of cholera, a devastating epidemic and pandemic disease. Despite its importance, the way of its global dissemination is unknown. V. cholerae is abundant in aquatic habitats and is known to be borne by copepods, chironomids and fishes. Our aim was to determine if fish-eating birds act as vectors in the spread of V. cholerae by consuming infected fish. We determined the existence of V. cholerae in the microbiome of 5/7 wild cormorants’ intestine. In three of these V. cholerae-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 56 publications
1
32
0
1
Order By: Relevance
“…cholerae from their tilapia fish prey, which is naturally inhabited by V . cholerae . Jubirt et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cholerae from their tilapia fish prey, which is naturally inhabited by V . cholerae . Jubirt et al .…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic strains of V. cholerae serogroup O1 were identified from two waterfowl species: Ardea herodias (great blue heron) and Larus delawarensis (rige-billed gull); the authors could not explain these findings, and the article was forgotten for more than 20 years [9] until Halpern et al [10] suggested that waterbirds might be vectors for V. cholerae. Recently, we have demonstrated that great cormorants (Phalacrocorax carbo) can be infected with V. cholerae from their tilapia fish prey, which is naturally inhabited by V. cholerae [11]. Jubirt et al [12] fed great egrets (Arda alba) with catfish contaminated by highly virulent A. hydrophila and then isolated it from the great egrets' faeces.…”
Section: Introductionmentioning
confidence: 99%
“…V. cholerae can form biofilms on chitinous substrates, such as the exoskeleton of crustaceans (8), and can colonize the gut of birds and fish, which may promote transmission in aquatic environments and perhaps contribute to human disease outbreaks (9,10). Within a human host, a complex set of signaling systems and external cues regulate colonization and disease factors, such as biofilm formation, chemotaxis-guided flagella, toxin-coregulated pili, several adhesins, and cell shape features, to ensure access of the microbe to the intestinal surface (11,12).…”
mentioning
confidence: 99%
“…Aquatic birds, especially migratory ones, play a significant role in the transportation of V. cholerae via two main routes. In the first route, birds may eat contaminated fish or other contaminated organisms in one pond and shed the pathogens in another area, as demonstrated by the presence of pathogenic V. cholerae in intestinal and fecal samples of aquatic birds [73,[87][88][89]. In the second route, chironomids and copepods, which are known to be reservoirs of V. cholerae, attach externally to the feather and feet of birds and facilitate the transport of pathogens [73].…”
Section: Aerial-dissemination Modesmentioning
confidence: 99%